Comparison of the SPF10-LiPA System to the Hybrid Capture 2 Assay for detection of Carcinogenic human papillomavirus genotypes among 5,683 young women in Guanacaste, Costa Rica - Safaeian, Mahboobeh (2007)
The objective of this analysis was to compare the performance characteristics of two human papillomavirus (HPV) DNA detections assays, the Hybrid Capture 2 assay (HC2) and the SPF10 assay, for the detection of carcinogenic HPV. Data are from the enrollment visits of women who participated in the randomized, double-blind, placebo-controlled phase III HPV16/18 Vaccine Trial in Guanacaste, Costa Rica. We compared the results of HC2 and SPF10 testing of cervical specimens. Since the line probe assay (LiPA) detection system does not distinguish between HPV type 68 (HPV68; which is targeted by HC2) and HPV73 (which is not targeted by HC2), for SPF10-LiPA, we defined the carcinogenic HPV types as the 12 HC2-targeted types (types 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59), HPV68/73, and the HC2-cross-reactive, carcinogenic type HPV66. The kappa values and the performance characteristics for the detection of cervical abnormalities were ascertained. Paired observations were available for 5,683 sexually active, young women (median age, 21 years). The prevalence of carcinogenic HPV types was 35% (n = 1,962) by HC2 and 35% (n = 2,003) by SPF10-LiPA. There were no differences in the prevalence of carcinogenic HPV types by HC2 and SPF10-LiPA among women with normal, atypical squamous cells of undetermined significance and high-grade squamous intraepithelial lesion cytology. Among women with low-grade squamous intraepithelial lesion cytology, HC2 was more likely to test positive than SPF10-LiPA for the carcinogenic HPV types (87% and 79%, respectively; P = 0.001) as a result of HC2 cross-reactivity with HPV types 40, 43, 44, 53, 54, 60, 70, and 74. The crude agreement between the two assays was 88%, with a kappa value of 0.75 (95% confidence limits, 0.73 to 0.76). We observed very good agreement between HC2 and SPF10-LiPA for carcinogenic HPV type detection.